Dedicated innovation systems to support the transformation towards sustainability: Creating income opportunities and employment in the knowledge-based digital bioeconomy - Andreas Pyka (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
In order to counter something to the most thrilling challenges of mankind at the beginning of the twenty-first century, production and consumption systems need to transform towards sustainability. We argue that the knowledge-based bioeconomy and digitalization are two promising technological approaches which require to be thought together in order to contribute to the transformation and to trigger the required technological dynamics. However, such a broad transformative process requires a participation of all societal stakeholders. Innovation systems in principle offer a framework for policy designs supporting the transformation, but they need to be extended to include the direction towards overcoming the lock-in in oil-based economic activities and mass consumption. For this purpose, we introduce the idea of a Dedicated Innovation System, which takes care of potential inertia due to the interest of established (oil-based) industries and consider the economic opportunities raised by social and responsible innovation. The transformation process will likely compensate for decreasing jobs in traditional sectors, which are increasingly replaced by robotics and artificial intelligence. The knowledge-based digital bioeconomy is likely to generate the emergence of new sectors with new employment opportunities, e.g. in periphery regions or in the emerging sharing-economy sector.
Keywords: 650; Dedicated innovation systems; Transformation; Digitalization; Bioeconomy; Innovation